2021
DOI: 10.1108/ijbpa-01-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Learning from plants: a new framework to approach water-harvesting design concepts

Abstract: PurposeThis paper's main objective is to focus on the water-harvesting ability of plants and try to implement a solution-based method to outline a plant-inspired design framework.Design/methodology/approachThe current paper aims to provide a step-by-step approach to the biological-inspired design by looking deeply at plants' mechanisms and features to harvest water and conduct a method to learn them in an organized way.FindingsIn addition to the proposed framework, the fundamental water-harvesting principles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Thus, there is a need to integrate plant mechanisms with the specific demands of building facades [29]. In the process of bio-inspiration, it is crucial to acknowledge the significance of biological characteristics and their relevance to achieving successful integration [64]. Plants exhibit remarkable abilities to control solar radiation through three key adaptive strategies: light harvesting (optimizing sunlight exposure), light regulation (minimizing sunlight exposure) and thermoregulation (temperature control).…”
Section: Solar Adaptation In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a need to integrate plant mechanisms with the specific demands of building facades [29]. In the process of bio-inspiration, it is crucial to acknowledge the significance of biological characteristics and their relevance to achieving successful integration [64]. Plants exhibit remarkable abilities to control solar radiation through three key adaptive strategies: light harvesting (optimizing sunlight exposure), light regulation (minimizing sunlight exposure) and thermoregulation (temperature control).…”
Section: Solar Adaptation In Plantsmentioning
confidence: 99%
“…Plants employ diverse strategies and incorporate various features to harvest solar radiation and optimize its utilization when required [64]. Esteso-Martínez et al [65] identified numerous structural and morphological characteristics related to light harvesting in certain plant species.…”
Section: Light Harvesting-maximizing Light Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical framework for plant-inspired design generation was proposed by Jalali et al [ 93 ] following a solution-based approach. This approach aimed to achieve water harvesting following a four-step plant-to-design path applied to an example of a building envelope panel.…”
Section: Biomimicry In Responsive Envelopes and Applicationsmentioning
confidence: 99%
“…Badarnah and Kadri (2015) designed a wall surface capable of harvesting water. Similarly, Jalali, Aliabadi, and Mahdavinejad (2021) developed a water harvesting facade proposal based on water harvesting strategies in plants. Mazzoleni (2013) also investigated water collection strategies in living things in nature and presented conceptual solutions.…”
Section: Introductionmentioning
confidence: 99%